Language assessment literacy from theory to practice - Tsagari, Dina (Cambridge Scholars Publishing, 2020)
The field of language testing and assessment has recognized the importance and underlying theoretical and practical underpinnings of language assessment literacy (LAL), an area that is gradually coming to prominence. This book addresses issues that promote the concept of LAL for language research, teaching, and learning, covering a range of topics. It brings together 14 chapters based on high-stakes and classroom-based studies authored by academics, professionals and researchers in the field. The text examines diverse issues through a multifaceted approach, presenting high-quality contribution.